The numinous and modernity : an interpretation of Rudolf Otto's philosophy of religion - Gooch, Todd A., 1967- (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2000)
The author traces the development of Rudolf Otto's attempt to construct a normative science of religion. This should respond to concerns facing Protestant theologians in Germany at the turn of the century. Moreover, he examines the reception of Otto's ideas after World War One. The volume contains name and subject indexes.